Pengaruh Penambahan Ubi Jalar (Ipomoea batatas) dan Ulva lactuca dalam Pakan terhadap Perubahan Warna dan Pertumbuhan Ikan Badut (Amphiprion percula) - Lamablawa, Yustina Martha Kindari; Lukas, Ade Yulita Hesti; Pasaribu, Wesly (Nusa Cendana University, 2024)
Saltwater ornamental fish have various species, many of which have been exported to various countries. One type of ornamental fish that can be kept in an aquarium is the clown fish (Amphiprion percula). However, clownfish tend to experience color fading when cultivated. This is caused by less than optimal food and lighting factors. The aim of this research is to determine the role of adding sweet potato flour (Ipomoea batatas) and ulva lactuca flour in feed to maintain the color of clownfish so that it remains as in nature and to support the growth of clownfish (Amphiprion percula). This research was carried out using four treatments and repeated three times, namely (1) F999 brand commercial feed, (2) 25% Ulva lactuca flour + 75% commercial feed, (3) 12.5% ​​Ulva lactuca flour + 12% sweet potato flour .5% + 75% commercial feed, (4) 25% sweet potato flour + 75% commercial feed. The parameters observed include color measurementsRed Green Blue (RGB) which is then converted to a color modelHue Saturation Brightness (HSB) and also growth. The research results show that fish color analysis usesHue Saturation Brightness (HSB), changes in hue values ​​tend towards yellow-orange colors. This shows similarities in maintaining color qualities found in clownfish in nature. However, there was no effect between different treatment on clown fish growth. The optimal dosage to achieve the desired fish color is to use 25% Ulva flour. Keywords: Amphiprion percula, sweet potato, ulva lactuca, color